A practical guide to e‐journal and e‐book supply – a UK perspective. Issue 1 (2014) - Mark Kluzek
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to report on current interlending and document delivery of e‐books and e‐journals in the UK and analyse the challenges encountered in such practices, using the experiences at King's College London as an example. Design/methodology/approach – The author uses a case study approach. Findings – Most UK libraries and higher education institutions negotiate the usage terms for their e‐resources through Jisc's NESLI2 model license agreement. While the terms of this agreement work relatively well for document delivery of e‐journal articles, allowing for secure electronic document transmission under prescribed circumstances, the interlending of e‐books remains problematic. Research limitations/implications – The paper provides insight into how UK document supply services can better use electronic holdings to offset the costs of requesting. It discusses the dilemma of e‐books and potential solutions. Practical implications – This will enable UK library professionals to better use e‐resources in a legally compliant way for the purpose of document delivery. It will explain to non‐UK library professionals how supplying from e‐resources works in the UK. Originality/value – The paper provides insight into how UK document supply services can better use electronic holdings to offset the costs of requesting. It discusses the dilemma of e‐books and potential solutions. <ack> <x xml:space="preserve"> Acknowledgements </x> This paper was originally presented at Interlend 2013, 27‐28 June, in Cardiff, Wales. </ack>